Lightweight TRC sandwich panels with sustainable diatomite-based core for energy retrofitting of existing buildings. Issue 2 (4th March 2021) - Colombo, Isabella G.; Colombo, Matteo; di Prisco, Marco; Galzerano, Barbara; Verdolotti, Letizia
ABSTRACT: Precast sandwich panels, characterized by external textile reinforced concrete (TRC) layers and an inner insulation core, represent a convenient system for energy retrofitting of existing façades. These elements fulfil all the requirements for façade systems and constitute a valid alternative to both external thermal insulation composite systems (ETICS) and ventilated façades. The main feature of this kind of panel is that it could be applied on an existing façade through four punctual connectors by means of a crane, without any scaffolding. The paper provides a solution that has been firstly designed within the European project 'EASEE' and it is now being developed in the 'Smart P.I.QU.E.R.' project, supported by Lombardy Region (Italy). Basing on the experience gained in the European project, the partners are trying to overcome some criticisms previously encountered, related to the use of expanded polystyrene as insulation material, the cost of the anchoring system and aesthetical issues related to TRC cracking. The main innovations concern: the development of a new eco-friendly insulation material based on inorganic diatomite; the optimization of TRC layers; the development of a new anchoring system. This paper focuses on the research developed at the material level referring to both external layers and insulating core.